Contingency consumer brand evaluations during recessions: a meta-analysis and systematic review - Palomino-Tamayo, Walter (2025)
Purpose: This study aims to conduct a meta-analysis and literature review on the effects of recessions on consumer brand evaluations. It examines how downturns influence various evaluation dimensions through the lens of Skinner’s contingency theory. Design/methodology/approach: This study reviewed literature from January 2000 to December 2023 for a psychometric meta-analysis, incorporating 155 effect sizes and 4,025,156 observations. It applied psychometric corrections and random-effects estimation. The literature review includes 47 studies. Findings: Recessions negatively affect consumer brand evaluations. Significant and predominantly negative relationships are observed between general brand impressions and brand-related consumer activity. This effect is significant and positive for brand commitment and not significant for brand-specific impressions. Brand familiarity, brand type and product convenience, considered contextual moderators, show a smaller and significantly negative effect on brand evaluations for familiar brands, real brands and low-convenience products. Methodological moderators have a significant and less negative effect in studies with study settings, data type and methodology. Originality/value: This study analyses the fragmented empirical literature on how changes in the economic environment affect firm and consumer behaviour towards consumer brand evaluations during recessions. It extends prior isolated meta-analyses of recessions and branding by introducing a novel theoretical framework based on Skinner’s contingency theory, offering new research directions.